2013
DOI: 10.3141/2330-10
|View full text |Cite
|
Sign up to set email alerts
|

Use of Data from Automatic Identification Systems to Generate Inland Waterway Trip Information

Abstract: Data from archived automatic identification systems in the Paducah, Kentucky, region were analyzed to produce reliable trip data for inland waterway vessels. Because of confidentiality concerns, few options for finding such trip data exist; this lack of data affects the quality of risk calculations. A combination of geographic information systems, relational databases, custom programming, and data visualization tools was applied to extract meaningful vessel traffic information and to detect events occurring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Onboard navigation devices transmit location and characteristics of vessels in real time to receivers on shore, satellite, buoy, and other vessels (U.S. Coast Guard n.d.). In the U.S., AIS is mandatory along the Ohio River, between Mileposts 593 and 606, and in the Lower Mississippi River, up to Milepost 254.5 (Dobbins and Langsdon 2013). Even though AIS is not required in all U.S. inland waterways, most vessels use the AIS transponder (DiJoseph and Mitchell 2015).…”
Section: Automatic Identification System Data (Ais)mentioning
confidence: 99%
“…Onboard navigation devices transmit location and characteristics of vessels in real time to receivers on shore, satellite, buoy, and other vessels (U.S. Coast Guard n.d.). In the U.S., AIS is mandatory along the Ohio River, between Mileposts 593 and 606, and in the Lower Mississippi River, up to Milepost 254.5 (Dobbins and Langsdon 2013). Even though AIS is not required in all U.S. inland waterways, most vessels use the AIS transponder (DiJoseph and Mitchell 2015).…”
Section: Automatic Identification System Data (Ais)mentioning
confidence: 99%
“…The fuzzy decision making matrix R is constructed in terms of n criteria and m RCOs. (12) (3) Establish the normalised fuzzy decision matrix.…”
Section: Fuzzy Topsis Methodsmentioning
confidence: 99%
“…Vessel traffic management systems in Europe inland waterways were assessed to tackle the problems of increasing waiting time at locks and inland ports due to traffic congestion and to explore the optimal use of the available capacity of inland shipping [11] . Valid trip data for inland waterway vessels were extracted from Automatic Identification System (AIS) in the Paducah for supporting analysis on port congestion in combination with other databases [12] . Besides, there was also research focusing on dealing with congestion issues from a management perspective.…”
Section: Waterway Congestionsmentioning
confidence: 99%
“…Very few studies on passenger transport by inland waterways have been reported in the literature. For instance, Dobbins and Langsdon (2013) reported the use of data from automatic identification systems to generate inland waterway trip information, allowing the information to be used to make risk analyses. Recently, environmental concerns and perceptions about comfort and safety have been introduced in the studies using hybrid mode, choicelatent variable modelling (Kim et al 2012;Márquez et al 2014).…”
Section: Introductionmentioning
confidence: 99%